ANALISIS KONTRAK KERJASAMA PENGANGKUTAN ALUMUNIUM ANTARA PT. INDONESIA ASAHAN ALUMUNIUM (PERSERO) DENGAN PT. KUALA JAYA SAMUDERA - SUWITO SITORUS (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Muhd. Yamin2. Suhaidi3. Hasim Purba Transportation contract is a consensual agreement in which a carrier makes a contract to transport goods from one place to another while the sender pays for the agreed freight. Cooperation agreement between PT. Indonesia Asahan Alumunium (Persero) as an aluminum company and PT. Kuala Jaya Samudera as a transportation company is a contract of transporting ingot (aluminum blocks). The research problems are as follows: how about the balance of agreement in the transportation contract of transporting ingot between PT. Indonesia Asahan Alumunium (Persero) and PT. Kuala Jaya Samudera, how about the implementation of the contract between the two companies, and how about the legal consequences of the contract between the two companies. Keywords: Cooperation Agreement, Transportation, Aluminum